A 6-year study of complicated urinary tract infections in southern China: prevalence, antibiotic resistance, clinical and economic outcomes - Li X; Chen Y; Gao WG; Ye H; Shen Z; Wen Z; Wei J (Dove Medical Press, 2017)
Xiaoyan Li,1,* Yunqin Chen,2,3,* Weiguo Gao,2 Hao Ye,2 Zhongchao Shen,2 Zehuai Wen,1 Jia Wei2 1Key Unit of Methodology in Clinical Research, Guangdong Provincial Hospital of Chinese Medicine, Guangzhou, 2R&D Information, AstraZeneca, Pudong, 3School of Life Sciences and Biotechnology, Shanghai JiaoTong University, Shanghai, China *These authors contributed equally to this work Abstract: Urinary tract infections (UTIs) are common nosocomial infections. This study evaluated the prevalence, pathogens, antibiotic resistances, clinical outcomes, and hospitalization costs associated with complicated UTIs in southern China, and risk factors delaying patient discharge. We retrospectively reviewed electronic medical records of 4,284 (61.4% women) complicated UTI-related hospitalizations from 2008 to 2013. Average patient age was 61.1 years and median hospital stay was 11 days. Pathogens were isolated from 1,071 urine and 148 blood specimens. Gram-negative bacteria were the most frequent and included Escherichia coli (48.2%), Klebsiella pneumoniae (9.5%), Pseudomonas aeruginosa (4.9%), and Proteus mirabilis (4.6%), while Enterococcus spp. (14.4%) was the most common Gram-positive bacteria causing UTIs. Both E. coli and K. pneumoniae showed high resistance rates (>45%) to wide-spectrum penicillins, cephalosporins, aztreonam, and ciprofloxacin. Resistances to beta-lactamase inhibitor/beta-lactam antibiotic combination were relatively lower. Imipenem, meropenem, and amikacin had the greatest activity against E.coli and K. pneumoniae. Recurrent infection was a risk factor for mortality. Age, sex, previous surgery, diabetes, and renal insufficiency were significant risk factors for delayed discharge (P<0.01). Response to initial treatment was associated with a lower cost. Initial empiric use of antibiotics least associated with resistance may reduce costs and medical resource usage. Keywords: urinary tract infection, Escherichia coli, antibiotic resistance, recurrent infection, length of stay, hospitalization cost